Estimating temptation and commitment over the life-cycle - Agnes Kovacs; Hamish Low; Patrick Moran (Institute for Fiscal Studies (IFS), 2020)
This paper estimates the importance of temptation (Gul and Pesendorfer, 2001) for consumption smoothing and asset accumulation in a structural life-cycle model. We use two complementary estimation strategies: first, we estimate the Euler equation of this model; and second we match liquid and illiquid wealth accumulation using the Method of Simulated Moments. We find that the utility cost of temptation is one-quarter of the utility benefit of consumption. Further, we show that allowing for temptation is crucial for correctly estimating the elasticity of intertemporal substitution: estimates of the EIS are substantially higher than without temptation. Finally, our Method of Simulated Moments estimation is able to match well the life-cycle accumulation profiles for both liquid and illiquid wealth only if temptation is part of the preference specification. Our findings on the importance of temptation are robust to the different estimation strategies.
Keywords: D12; D91; E21; G11; R21; 330; life-cycle; temptation preferences; housing; estimating Euler equations